Effects Of Use Of Mobile Banking And Administrative Costs On Customer Satisfaction at Bank Syariah Indonesia Rantauprapat Branch Offices - Siregar, Nurintan Asyiah; Safri, Hayanuddin; Syafrizal, Andre; Gulo, Nur’ainun (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
This study aims to determine the effect of using Mobile Banking and administrative cost on customer satisfaction at Bank Syariah Indonesia Rantauprapat Branch Offices, both partially and simultaneously, Determining the sample technique using Arikunto’s opinion with a total of 40 people and the method of analysis used is descriptive analysis method, multiple linear regression analysis, and hypothesis testing. The results of partial hypothesis testing (t-test) show that Mobile Banking (X1) and administrative costs have a positive and significant effect on Customer satisfaction at Bank Syariah Indonesia Branch offices, with a t count Mobile Banking variable value of3.018 while t table is 1.689 (t count) bigger than t table). Meanwhile, for the variable administration costs, the t-count is 2.608, while the t-table is 1.689 (t-count is greater than t-table). The results of simultaneous hypothesis testing (F test) show that Mobile Banking (X1) and administrative costs (X2) have a positive and significant effect on customer satisfaction at Bank Syariah Indonesia Rantauprapat Branch Offices, with an f count of 10.371 while a f table of 2.64 (f count over larger than f table). The test results for the coefficient of determination (R2) show that the Adjusted R square value is 0,419 or 41.9% indicating that Mobile Banking and Administrative Fees simultaneously contribute to customer satisfaction of 41.9%